Anticoagulant Related Nephropathy Only Partially Develops in C57BL/6 Mice: Hematuria Is Not Accompanied by Red Blood Cell Casts in the Kidney - Medipally, Ajay K.; Xiao, Min; Qaisar, Shahzeb; Satoskar, Anjali A.; Ivanov, Iouri; Rovin, Brad; Brodsky, Sergey V. (Frontiers in Medicine, 2021)
Anticoagulant related nephropathy (ARN) may develop in patients on anticoagulation therapy. Rats with 5/6 nephrectomy treated with different anticoagulants showed acute kidney injury (AKI) and red blood cell (RBC) casts in the tubules similar to ARN in humans. The aim of the current study was to investigate the feasibility to induce ARN in mice. C57BL/6 5/6 nephrectomy mice were treated with warfarin and dabigatran 3 weeks after the ablative surgery for 7 days. Two doses of each anticoagulant were used. All anticoagulants resulted in serum creatinine and hematuria increase. Mortality was 63% in 5.0 mg/kg/day warfarin but only 13% in 2.5 mg/kg way warfarin or in 400 mg/kg/day dabigatran and 0 in 200 mg/kg/day dabigatran. In spite of increasing hematuria, RBC tubular casts were not seen in treatment with any anticoagulant. 5/6 nephrectomy murine model in C57BL/6 mice only partially reproduces ARN in terms of increasing serum creatinine and hematuria, but there is no RBC tubular casts in the remnant kidney.